Proposal for a Conceptual Model of Organizational Viability for Foundations in Spain - Villar, Sissy Anne Álvarez; García-Granero, Ana (Journal of Ecohumanism, 2024)
Foundations are organizations that are part of the Third Sector while playing an important social role, acting as amplifiers of assistance for the benefit of minority groups, as well as first-line aid organizations in times of crisis. This paper seeks to identify the aspects that influence the organizational viability of foundations in Spain using qualitative research techniques by which key informants in the sector were interviewed through the use of semi-structured questionaries. Responses were analyzed in a matrix structure, obtaining the keywords in order to summarize the information and concepts provided. Then, this content was analyzed using ATLAS.ti software, obtaining a “word cloud”, which served as an inspiration to propose a conceptual model. This model, as its main result, seeks to reveal the aspects and particularities of foundations in Spain, taking into account internal and external characteristics, their immediate environment, and the regulations and norms. Finally, the challenges to be faced by the sector are presented, encouraging support entities such as universities, research centers, and second-order organizations, together with the Public Administration, to take action in those gaps that must be avoided.